Peran Antitrombin III sebagai Penanda Sepsis pada Anak - Indah Nur Lestari; Chairul Yoel; Munar Lubis; Rina Amalia C Saragih; Gema Nazri Yanni; Yunnie Trisnawati; Aridamuriany D Lubis; Badai Buana Nasution (PT Kalbe Farma Tbk., 2023)
Sepsis is a life-threatening organ dysfunction caused by dysregulation of the immune response to infection. Antithrombin III is a single plasma bound glycoprotein and include a class of serine protease (serpine) inhibitors; its synthesis in the liver decreases during sepsis.